Handbook for social justice in counseling psychology : leadership, vision, and action - Toporek, Rebecca L. (Rebecca Louisa), 1963-; Gerstein, Lawrence H.; Fouad, Nadya A.; Roysircar, Gargi; Israel, Tania (Counseling and psychotherapy transcripts, client narratives, and reference works., 2006)
'The Handbook for Social Justice in Counseling Psychology' provides counselling psychology students, educators researchers, and practitioners with a conceptual 'road map' of social justice and social action that they can integrate into their professional identity, role, and function.